PEMBUATAN PAKAN TERNAK MANDIRI KELOMPOK TANI TERNAK UNGGAS DESA LAKAT KECAMATAN KUATNANA KABUPATEN TIMOR TENGAH SELATAN - Marten L. Lano; Jemmy J.S. Dethan (Bajang Institute, 2022)
The Tafeun Tenab Farmer's Group is located in Lakat Village, South Central Timor. This group has 8 sub groups with 8 members each. Sub groups 1 and 2, cultivate broiler chickens with a monthly turnover of Rp. 13.800.000,-. The problem faced is the low profit caused by the high price of broiler feed. The price of feed per sack containing 50 kg at the location is Rp. 460,000, - and for 300 heads / month 15 sacks of feed are needed. With the DOC/box price of IDR 1,100,000 and the need for vaccines and medicines, a minimum capital of IDR 12,500,000 is required. From the turnover and capital that must be prepared, the profit margin is only around IDR 1,300,000. Given these problems, efforts are needed to provide cheaper and quality feed. Because it is induced by feed technology with local ingredients from corn and bran available which is added with concentrate at a relatively cheap price. The technology that was induced was in the form of feed manufacturing technology, corn flour equipment, mixing equipment and pellet printing. The results of the application of independent animal feed technology are produced: 1). There is a savings in the cost of procuring feed up to 70% or from the original Rp. 6,900,000/300 head/month to Rp. 5,655,000/300 head/month. 2). Availability of 2 units of corn grinder, 2 units of mixer and pellet press and 3). There is a transfer of knowledge and skills in making poultry feed independently and sustainably in partner groups.